ḤADĪṠ MEMBACAAL-FĀTIḤAH KETIKA ṢALĀT - Ernawati Beru Ginting (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
The difference of opinion in this generation is seen between Abū Ḥanifah and al-Syafi''i about practicing hadiṡ ahad. Abū Ḥanifah rejects hadiṡ ahad when it is contrary to the practice of sahabat, Kilani concludes in his Thesis, the principle of Abū Ḥanifah about accepting hadiṡ ahad if there is an indication of the practice of the companions if hadiṡ ahad is in accordance with their practice then it is acceptable and if it is contrary it will be rejected. While al-Shafi''i accepted hadiṡ ahad without having to be tested by the practice of sahabat, he commented, whether or not the practice of partial sahabat with hadiṡ does not cause us anxiety because hadiṡ establishes its own sahih. Based on the above problems, the author wants to examine the understanding of scholars regarding the recitation of al-Fatihah at the time of salat, in this study the author will study using thematic studies (mauḍū''i). The method used is library research.From the previous description, it can be concluded that Surah al-Fatihah is really the main letter in the Qur''an, so reading it for musalli becomes an obligation. However, in congregational prayers, the recitation of imam has represented the recitation of makmum including the recitation of al-Fatihah. According to Imam Ḥanafi reciting surah al-Fatihah in salat is not a pillar but a compulsory salat, and salat is valid without reciting surah al-Fatihah and supplemented with sahwi prostration, which is the pillar of salat according to Imam Ḥanafi is a verse of the Qur''an in general, at least 3 short verses and 1 long verse